A política de segurança alimentar e nutricional em Porto Alegre/RS : avanços e retrocessos nos programas e serviços - Rosa, Priscilla Rohmann da Silva (2023)
Brazil is one of the largest food producers in the world, but a large part of its population does not have access to basic foodstuffs for their survival. The social forms that occurred in the decades resulted in the reduction of the last poverty and, consequently, of food insecurity, with an improvement in access and variety in food, as well as the guarantee of the average availability of calories for consumption. Even with strategies created to make it possible for Brazil to leave the Hunger Map in 2014, as of 2016 with the reduction of resources for income transfer programs, lack of incentives for family farming and the slowdown in economic growth, there was an accentuation of poverty and social vulnerability in the country, a situation evidenced by the 2017-2018 Household Budget Survey, which showed a regression of hunger data to 2004 levels. Food and Nutrition Security public policies in Porto Alegre, from 2016 to 2021, with a view to contributing with credits for the improvement of policies in this segment. This study was carried out based on the dialectical-critical method, based on historical materialism and has as its central categories: totality, historicity, differences and mediation. A literature review and interviews were carried out using an interview script, using an intentional sample of 5 professionals working in the municipal policies, these being members of the municipal or state food safety councils, the data obtained were analyzed from according to the content analysis technique, according to Moraes (1999). The area of food and nutrition, as well as the area of social assistance, has always been on the margins of public social policies.Programs, projects and policies in the area of food and nutrition, historically, overlapped with each other and without articulation with other areas, showing that integration and the intersectoral approach are not being properly contemplated in their planning.